2015
DOI: 10.1021/acs.orglett.5b01430
|View full text |Cite
|
Sign up to set email alerts
|

Straightforward Synthesis of Purine 4′-Alkoxy-2′-deoxynucleosides: First Report of Mixed Purine–Pyrimidine 4′-Alkoxyoligodeoxynucleotides as New RNA Mimics

Abstract: Purine and pyrimidine 4'-alkoxy-2'-deoxynucleosides were efficiently prepared from nucleoside 4'-5'-enol acetates in three steps by N-iodosuccinimide promoted alkoxylation, hydrolysis, and reduction followed by conversion to phosphoramidite monomers for the solid-phase synthesis of the oligonucleotides. Fully modified 4'-alkoxyoligodeoxynucleotides, which are characterized by a prevalent N-type (RNA-like) conformation, exhibited superior chemical and nuclease resistance as well as excellent hybridization prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…Earlier reports of 4′- C -modified nucleotides, including 4′- C -OMe-2′-deoxynucleotides ( 17 , 18 ) and 2′-F,4′- C -F pyrimidine nucleotides ( 19–21 ) and their incorporation into oligonucleotides support the notion of a preference for a Northern sugar pucker. The thermodynamic stability of RNA duplexes containing such nucleotides is similar to that of the native counterparts ( 21 ).…”
Section: Introductionmentioning
confidence: 85%
“…Earlier reports of 4′- C -modified nucleotides, including 4′- C -OMe-2′-deoxynucleotides ( 17 , 18 ) and 2′-F,4′- C -F pyrimidine nucleotides ( 19–21 ) and their incorporation into oligonucleotides support the notion of a preference for a Northern sugar pucker. The thermodynamic stability of RNA duplexes containing such nucleotides is similar to that of the native counterparts ( 21 ).…”
Section: Introductionmentioning
confidence: 85%
“…It is reported that the strong anomeric effect of the exocyclic oxygen atom attached to the C4′ carbon can drive the sugar part of 2′-deoxynucleotides toward the RNA-like C3′- endo (north) conformation. This conformational behavior is highly beneficial to the binding affinity to complementary RNA [ 15 , 16 ]. Moreover, Damha et al [ 17 ] demonstrated that introduction of 4′-F into 2′-F–araU switched the preferred sugar conformation from DNA-like to RNA-like by the similar anomeric effect of 4′-F.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it was predicted that the 4′- C -alkoxy-2′-F–arabinonucleotide derivatives would also pre-organize the sugar ring toward a north conformation, and enhance the hybridization properties for antisense oligonucleotides. Moreover, C4′ modifications on the ribose moiety, such as 4′-S [ 11 ], 4′- C -OMe [ 15 , 16 ], and 4′- C -aminomethyl [ 10 , 18 ], are reliable strategies to increase nuclease resistance. In particular, the C4′-modified 2′-F–uridine derivative, 2′-F,4′- C α-OMe–uridine, which was recently reported by Damha et al [ 19 ], was able to increase nuclease resistance due to the close proximity between 4′-OMe substituent and the vicinal 5′- and 3′-phosphate group.…”
Section: Introductionmentioning
confidence: 99%
“…In this unit, a robust synthetic protocol is described, providing phosphoramidites of RNA‐like 4′‐methoxy 2′‐deoxynucleosides, which are useful as monomers for the synthesis of oligonucleotides on solid phase according to conventional phosphoramidite chemistry. The protocol is based on previously published work (Petrová et al., ), and contains detailed procedures for the synthesis of phosphoramidite monomers of 4′‐methoxy 2′‐deoxyadenosine, 2′‐deoxyguanosine, 2′‐deoxycytidine, thymidine, and 2′‐deoxyuridine, respectively (Fig. and Table ).…”
Section: Introductionmentioning
confidence: 99%
“…In this unit, a robust synthetic protocol is described, providing phosphoramidites of RNA-like 4methoxy 2 -deoxynucleosides, which are useful as monomers for the synthesis of oligonucleotides on solid phase according to conventional phosphoramidite chemistry. The protocol is based on previously published work (Petrová et al, 2015), and contains detailed procedures for the synthesis of phosphoramidite monomers of 4 -methoxy 2deoxyadenosine, 2 -deoxyguanosine, 2 -deoxycytidine, thymidine, and 2 -deoxyuridine, respectively ( Fig. 1.38 The Basic Protocol describes the synthesis of 4 -methoxy 2 -deoxynucleoside phosphoramidites 7a-e for A, G, C, T, and U from the corresponding 4 ,5 -enol acetates 3a-e. 4 -Methoxy dNs 4a-e, obtained in one pot by successive N-iodosuccinimide-promoted methoxylation, hydrolysis, and reduction, are converted to 3 -O-phosphoramidites by a routine three-step procedure.…”
Section: Introductionmentioning
confidence: 99%